Immunoliposomes: Synthesis, Structure, and Their Potential as Drug Delivery Carriers - Sandeep, Divya (2020)
Immunoliposomes have emerged as attractive drug targeting vehicles for cancer treatment. This review presents the recent advances in the design of immunoliposomes encapsulating a variety of chemotherapeutic agents. We provided an overview of different routes that can be used to conjugate antibodies to the surfaces of liposomes, as well as several examples of stimuli-responsive immunoliposome systems and their therapeutic potential for cancer treatment.